2020
DOI: 10.2174/1573403x16666200214104122
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sarcopenic Obesity and Metabolic Syndrome in Adults: A Systematic Review and Meta-Analysis

Abstract: Background: In the last two decades, a new phenotype termed Sarcopenic Obesity (SO), in which sarcopenia and obesity coexist, has emerged. Objective: The aim of this systematic review and meta-analysis was first to assess the prevalence of Metabolic syndrome (Mets) among individuals with and without SO, and second, to determine if SO may increase the relative risk of Mets. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…The pooled OR showed that sarcopenic obesity was associated with a 38 % increase in odds of type 2 diabetes compared with those without sarcopenic obesity Khadra et al (76) Meta-analysis n 11 308 Twelve studies Men and women…”
Section: Various Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pooled OR showed that sarcopenic obesity was associated with a 38 % increase in odds of type 2 diabetes compared with those without sarcopenic obesity Khadra et al (76) Meta-analysis n 11 308 Twelve studies Men and women…”
Section: Various Measurementsmentioning
confidence: 99%
“…Sarcopenic obesity was significantly associated with a 38 % increase in risk of type 2 diabetes compared with those without sarcopenic obesity (OR 1•38, 95 % CI 1•27, 1•50), but results should be interpreted with caution as the majority of studies were cross-sectional. A meta-analysis has also been carried out to synthesise the results of studies assessing the associations between sarcopenia obesity and the metabolic syndrome, including twelve studies with a total of 11 308 overweight or obese adults (76) . Pooled analysis showed that sarcopenic obese participants did not have a significantly increased risk of the metabolic syndrome (risk ratio 1•08, 95 % CI 0•99, 1•17) compared with those with obesity only.…”
Section: Various Measurementsmentioning
confidence: 99%
“…В систематическом обзоре и метаанализе, выполненном Khadra D. и соавт. (2019), включавшем 11 308 пациентов обоих полов с избыточной массой тела или ожирением, было показано, что СД2 и СО имеют сильную патогенетическую взаимосвязь [21].…”
Section: этиология и патогенез соunclassified
“…The changes in body composition (affecting mainly protein), decreasing turnover of structural proteins [ 677 ], and thus, reducing their reposition and functionality, do not necessarily affect body lipid stores. Thus, sarcopenia can often develop while maintaining obesity (e.g., sarcopenic obesity) [ 678 , 679 ]. The obese can become sarcopenic and frail while maintaining their main energy (TAG) stores full, with a largely unused mass of fat which constitutes an additional burden [ 680 ].…”
Section: The Use Of Androgens For the Treatment Of Functional Disordersmentioning
confidence: 99%